« Sortez des clichés ! Regard sur des patrimoines vivants » - Valérie Perlès (In Situ)
The UNESCO convention on the intangible cultural heritage introduces a novel redistribution of balance, between researchers and local populations, who cease to be objects of study or potential visitors and become major players. The French federation of eco-museums and museums of society (FEMS) was curious then to see how these museums, which have always addressed questions of living cultural expressions, of memory and its transmission, are taking advantage of a new tool for heritage protection. Two photographers, Jean-Christophe Bardot and Olivier Pasquiers were commissioned to realise a series of reportages on themes suggested by members of the FEMS network. The project has a documentary ambition, but also aims at producing a sensitive and distanced interpretation, which is neither the museum discourse nor that of the communities concerned. It is a third way, so to speak, where different points of view on the intangible cultural heritage can meet.